Trends in IVIG use at a tertiary care Canadian center and impact of provincial use mitigation strategies: 10‐year retrospective study with interrupted time series analysis. Issue 6 (27th March 2019) - Murphy, Malia S.Q.; Tinmouth, Alan; Goldman, Mindy; Chassé, Michaël; Colas, Jo Ann; Saidenberg, Elianna; Shehata, Nadine; Fergusson, Dean; Forster, Alan J.; Wilson, Kumanan
Abstract : BACKGROUND: Intravenous immunoglobulin (IVIG) is a fractionated plasma product used to treat a range of autoimmune or inflammatory conditions, as well as immunodeficiency. Demand for this high‐cost product is increasing worldwide. Understanding historical changes in IVIG use is important for inventory management and demand forecasting as well as for the development of initiatives aimed at optimizing blood product use. STUDY DESIGN AND METHODS: This was a 10‐year retrospective cohort study of all patient encounters involving an IVIG transfusion from 2007 to 2016 at a four‐site tertiary care hospital in Ontario, Canada. IVIG use was reported, including number of hospital encounters and amounts of IVIG prescribed. An interrupted time series analysis was performed to evaluate temporal changes in product use coinciding with the release of 2009–2010 provincial initiatives to optimize IVIG. RESULTS: A total of 1, 658, 159.50 g of IVIG was administered from 2007 to 2016. Total annual volume administered initially decreased after implementation of new policies (−2032 g/quarter). The number of IVIG patient encounters also decreased (−49.8 encounters/quarter) but was mirrored by an increase in the total volume administered per patient encounter (+0.88 g/quarter). Use increased 820 g/quarter from 2013 to 2016 but was 21% lower than projected before implementation of provincial policies. CONCLUSION: Trends in IVIG use show ongoing increases in the number of patients treated with the product. Development and implementation of provincial initiatives to optimize IVIG use coincided with significant short‐term changes at a large tertiary care hospital. Novel initiatives aimed at dose minimization and prescription rationalization for this therapy are needed on local as well as larger scales.